Lp(a)-Lowering Agents in Development: A New Era in Tackling the Burden of Cardiovascular Risk - Katsiki, Niki; Vrablik, Michal; Banach, Maciej; Gouni-Berthold, Ioanna (Pharmaceuticals, 2025)
Lipoprotein (a) [Lp(a)] has been recognized as an independent, inherited, causal risk factor for atherosclerotic cardiovascular disease (ASCVD) and aortic valve stenosis, thus representing a major target of residual CV risk. Currently, no drug has been officially approved for lowering Lp(a) levels, and in clinical practice, Lp(a) is mainly used to (re)define CV risk, particularly in individuals at borderline CV risk and people with a family history of premature coronary heart disease, according to various guidelines. Specific Lp(a)-targeted antisense oligonucleotides (ASOs) and small interfering RNA (siRNA) agents have been developed to produce substantial Lp(a) reductions via the inhibition of apo(a) synthesis in the liver. These drugs are conjugated to N-acetylgalactosamine (GalNAc) to ensure their binding to asialoglycoproteins, which are specifically expressed on the surface of the hepatocytes. Such drugs include pelacarsen (an injectable ASO) and olpasiran, zerlasiran, and lepodisiran (injectable siRNA agents). Muvalaplin represents another therapeutic option to lower Lp(a) levels, since it is an oral selective small molecule inhibitor of Lp(a) formation, thus potentially exerting certain advantages in terms of its clinical use. The present narrative review summarizes the available clinical data on the efficacy and safety of these investigational Lp(a)-lowering therapies, as reported in phase 1 and 2 trials. The effects of these drugs on other [aside from Lp(a)] lipid parameters are also discussed. The phase 3 CV trial outcomes are ongoing for some of these agents (i.e., pelacarsen, olpasiran, and lepodisiran) and are briefly mentioned. Overall, there is an urgent need for evidence-based guidelines on Lp(a) reduction in daily clinical practice, following the results of the phase 3 CV trials, as well as for establishing the ideal Lp(a) quantification method (i.e., using an apo(a) isoform-independent assay with appropriate calibrators, reporting the Lp(a) level in molar units).